Accessing educational approaches to Building Information Modeling (BIM) at construction management master studies in Croatia - Sonja Kolarić; Mladen Vukomanović; Dina Stober; Zlata Dolaček-Alduk (Tehnički Vjesnik, 2017)
Building Information Modelling (BIM) is the current trend of the Architectural, Engineering and Construction (AEC) industry today. For its successful adaptation, education and standardization are one of the key success factors. In education, BIM provides development of students’ critical way of thinking and enables them to understand the complexity of the construction industry. As there is no accurate information about BIM education at Croatian universities, the aim of this paper was its implementation at the University J. J. Strossmayer of Osijek and the University of Zagreb. We have found that the current schemes enabled students to understand the BIM concept and how BIM changes and fosters the work processes in construction projects. However, we have also identified the deficient knowledge in coordination, interoperability and clash detection. Therefore, the future work involves extension on collaboration tools and covering the above mentioned, missing knowledge areas.